Size estimates of unknown boundaries with a Robin-type condition. Issue 4 (16th March 2017) - Di Cristo, Michele; Sincich, Eva; Vessella, Sergio
Abstract : We deal with the problem of determining an unknown part of the boundary of an electrical conductor that is inaccessible for external observation and where a corrosion process is going on. We obtain estimates of the size of this damaged region from above and below.